1982
DOI: 10.2224/sbp.1982.10.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Effects of Father Absence on Children and Their Mothers

Abstract: This study investigates the effects of the presence or absence of the father in the home in two samples of New York City families: a sample of 1000 Welfare AFDC families and a subsample of lower-middle income families from a random cross-section sample. The effects of natural fathers, surrogate fathers and absent fathers were examined for mothers and their children, respectively. The variables included measures derived from mothers' home interviews: 18 child behavior factors and 13 familial factors. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Interactions were detected in 39 of the 44 family studies for at least one measure of familial and SN risk. Twenty-three of the 39 studies that uncovered interactions indicated that familial risk factors were more detrimental in environments characterized by high-SN risk, nine indicated the reverse (Coley & Hoffman, 1996;Coley, Morris, & Hernandez, 2004;Eamon, 2001;Furstenberg, Cook, Eccles, Elder, & Sameroff, 1999;Gorman-Smith et al, 1999;Kierkus & Baer, 2003;McCarthy, Gersten, & Langner, 1982;Miller, Wasserman, Neugebauer, Gorman-Smith, & Kamboukos, 1999;Simons et al, 2002), and seven were supportive of both positions for various subpopulations or measures (Austin, 1978;Berger & Simon, 1974;Eisenberg, Langner, & Gersten, 1975;Gorman-Smith et al, 2000;Lamborn, Dornbusch, & Steinberg, 1996;Shaw, Criss, Schonberg, & Beck, 2004;Williams, Bean, & Curtis, 1970). Interestingly, seven of the nine studies that reported weaker effects in settings with high-levels of SN risk and four of the seven studies that were supportive of both positions for some measures or subpopulations demonstrated restricted range for SN risk.…”
Section: Familial Risk Factorsmentioning
confidence: 99%
“…Interactions were detected in 39 of the 44 family studies for at least one measure of familial and SN risk. Twenty-three of the 39 studies that uncovered interactions indicated that familial risk factors were more detrimental in environments characterized by high-SN risk, nine indicated the reverse (Coley & Hoffman, 1996;Coley, Morris, & Hernandez, 2004;Eamon, 2001;Furstenberg, Cook, Eccles, Elder, & Sameroff, 1999;Gorman-Smith et al, 1999;Kierkus & Baer, 2003;McCarthy, Gersten, & Langner, 1982;Miller, Wasserman, Neugebauer, Gorman-Smith, & Kamboukos, 1999;Simons et al, 2002), and seven were supportive of both positions for various subpopulations or measures (Austin, 1978;Berger & Simon, 1974;Eisenberg, Langner, & Gersten, 1975;Gorman-Smith et al, 2000;Lamborn, Dornbusch, & Steinberg, 1996;Shaw, Criss, Schonberg, & Beck, 2004;Williams, Bean, & Curtis, 1970). Interestingly, seven of the nine studies that reported weaker effects in settings with high-levels of SN risk and four of the seven studies that were supportive of both positions for some measures or subpopulations demonstrated restricted range for SN risk.…”
Section: Familial Risk Factorsmentioning
confidence: 99%
“…Further support for the hypothesis that the single-parent family enhances delinquent behavior comes from four other studies. McCarthy et al (1982) found that, for families on welfare, father absence was related to smoking and truancy. However, their unofficial measure of delinquency was particularly weak as it was based on reports provided by the mother rather than the adolescent.…”
Section: Single-parent Familiesmentioning
confidence: 99%
“…Using an indirect measurement of delinquency, Steinberg (1987) found that youth from families containing a stepparent were more susceptible to antisocial peer pressure than either father-absent or intact families. An investigation of lowincome families by McCarthy et al (1982) revealed that, for low-income families not on welfare, the most delinquent children were those in families with a surrogate father. However, their analysis was limited to smoking and truancy.…”
Section: Stepfamiliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also concluded that for youths like Sabrina who are raised in a female-headed African American home, chances of achieving success are poor based on indicators such as drug use or involvement in criminal activities (McCarthy, Gersten & Langner, 1982;Dornbush, 1985;Steinberg, 1987;Flewelling & Bauman, 1990;Needle, Su, & Doherty, 1990). Finally, many studies have concluded that for African American youths like Sabrina who live in low-income urban neighborhoods, their chances of involvement in criminal activities, especially drug trafficking are very high compared to their middle class counterparts (Whitehead, Peterson and Kaljee, 1994;Weinfurt andBush, 1995: Ricardo, 1994;Li, Stanton, Black and Fiegelman, 1996;Okundaye, 1999).…”
Section: Introductionmentioning
confidence: 99%